Analysis of status of logistics in chemical industry enterprises in the Czech Republic - Vlčková, Vladimíra; Kubínová, Jana (University of Pardubice, 2011)
This paper deals with an analysis of the status of logistics management in the chemical industry enterprises in the Czech Republic. The analysis starts from our own survey. The most important factors of the logistics development with regard to the needs of assessment of the implemented survey, particularly to understanding of the level of logistics in individual enterprises are given. The analysis is focused on the organizational arrangement of logistics activities, the level of perception of the logistics system by managers, transformation changes within companies affecting logistics, utilization of logistics technologies, information systems and quantitative methods for management of logistics processes. Gradual qualitative shift in the logistics management in the chemical industry businesses is obvious. However reluctance and distrust of data and information sharing within the supply chain are still persisting.